Case report: First report of isolated central nervous system lymphoblastic crisis in a child with chronic myeloid leukemia on dasatinib therapy - Jo, Suejung; Yoo, Jae Won; Kim, Seongkoo; Lee, Jae Wook; Im, Soo-Ah; Cho, Bin; Chung, Nack-Gyun (Frontiers in Oncology, 2023)
Most children with chronic myeloid leukemia (CML) present with the chronic phase (CML-CP) at diagnosis, exhibiting an excellent treatment response to contemporary tyrosine kinase inhibitors (TKIs). However, despite TKI therapy, patients with CML-CP may progress to blastic crisis (BC). CML-BC rarely occurs in extramedullary sites, and isolated central nervous system (CNS) BC is an extremely rare condition. It may with present various neurologic symptoms that necessitates differential diagnosis from other causes such as TKI toxicity. Information on the diagnosis and treatment of this condition is lacking, as are well-established diagnostic criteria. Here, we report a case of isolated CNS lymphoblastic crisis in a child with CML-CP who was treated with dasatinib. The patient, an 8-year-old girl, was admitted owing to visual disturbance and severe headache. We highlight the importance of a CSF study for the differential diagnosis of CNS BC in patients with CML-CP who present with common neurologic symptoms during TKI therapy.